RESEARCH ON WATERSIDE URBAN OPEN SPACES IN RESIDENTIAL ENVIRONMENT OF LOWLAND CITY- A CASE STUDY OF SAGA - J. Ge; M. Gong; Q. Ye; K. Hokao (Lowland Technology International, 2008)
In this research, waterside spaces of a lowland city were studied from the interactive aspect of physical conditions, users’ consciousness/behaviors, and waterside design. Firstly, using Saga City as a case study, the overall conditions of waterside spaces in the city and their physical properties were made clear through site surveys. Then, by Semantic Differential (SD) survey and analysis, three main image components of waterside spaces in urban open spaces and residential environment of lowland cities were found: natural view, environmental arrangement, and urban density. Next, through Cluster Analysis, five image types of waterside spaces and their characteristics were obtained. Furthermore, the behavior tendency of each type of waterside was also analyzed. Finally, on the basis of above surveys and analysis, environmental designs were performed in the five types of waterside, and a SD simulation was conducted to verify the effectiveness of the design. The effective reformation methods for different types of waterside spaces were discussed in order to improve the image of waterside and to activate users’ behaviors. The results of this research could be applied directly in the development and improvement of waterside spaces for practice.